2022
DOI: 10.1002/ett.4569
|View full text |Cite
|
Sign up to set email alerts
|

Optimal power allocation for non‐orthogonal multiple access enabled full‐duplex underlay cognitive relay networks under partial relay selection

Abstract: This article considers non-orthogonal multiple access (NOMA) enabled full-duplex (FD) underlay cognitive relay networks (ie, NOMA-FDCRNs) with partial relay selection scheme. The secondary network, where NOMA is used, consists of a secondary base station (SBS) sending messages to two secondary users (SUs), that is, a near SU (SU1) and a far SU (SU2), by utilizing a dedicated relay selected from a set of FD decode-and-forward nodes. We obtain analytical expressions for the outage probabilities (OPs) of the SUs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This system enables multiple SUs to send and receive signals concurrently while still adhering to primary interference power limitations. The work in [13] explores the performance of a NOMA based underlay CR framework with partial relay selection (PRS). In this setup, the secondary network employs NOMA, utilizing K half-duplex (HD), decode-and-forward (DF) relays to assist the SBS in serving SUs.…”
Section: A Related Workmentioning
confidence: 99%
“…This system enables multiple SUs to send and receive signals concurrently while still adhering to primary interference power limitations. The work in [13] explores the performance of a NOMA based underlay CR framework with partial relay selection (PRS). In this setup, the secondary network employs NOMA, utilizing K half-duplex (HD), decode-and-forward (DF) relays to assist the SBS in serving SUs.…”
Section: A Related Workmentioning
confidence: 99%
“…Moreover, regarding merging the three techniques in one system, that is, MIMO, NOMA, and CR, the performance of the cooperative sensing on the conventional and superior selective reporting types are investigated in reference 18, in which the error probability of the false alarm is derived and optimization constraints are studied for the sake of enhancing the sum rates of the proposed schemes. In reference 19, NOMA with underlay cognitive radio based on in‐band full duplex is proposed and investigated, where a scheme of partial selection of decode‐and‐forward relays is considered, and expressions for obtaining the optimal coefficients of the power allocation are evaluated for maximizing the throughput of the secondary network. Furthermore, the authors in reference 20 suggest the utilization of multiple carrier filter‐band‐based spectral sensing of cooperative NOMA‐CR networks.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results demonstrated that the system performance can be enhanced using multiple relays. An optimal power allocation scheme using partial relay selection was considered in [51] for the sake of enhancing the performance of underlay CRNs. In this work, NOMA was used for transmission and one relay was selected among several DF relays.…”
Section: Introductionmentioning
confidence: 99%